2020
DOI: 10.1021/acsbiomaterials.0c00194
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Calcium Phosphate Mineralization by Peptides with Adjacent Oppositely Charged Residues

Abstract: Calcium phosphate mineralizing peptides are of special importance for dental and orthopedic applications, such as caries remineralization and improved osteointegration. Uncovering the mechanism of action for such peptides is an ongoing challenge with the aim of a better fundamental understanding of biomineralization processes and developing optimized peptides for clinical use. It has recently been reported that "adjacent oppositely charged residue" motifs are found abundantly in cation binding, inorganic surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
3
10
0
1
Order By: Relevance
“…These seemingly contradicting results emphasize the complexity of these systems. Moreover, it was previously shown that conformation has a role in the interaction with solid surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…These seemingly contradicting results emphasize the complexity of these systems. Moreover, it was previously shown that conformation has a role in the interaction with solid surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…The peptide used in this study is proposed to act by attracting the available calcium and phosphate ions, thus, creating local supersaturation zones. 24 In contrast, existing products provide the fluoride (and calcium and phosphate) to a relatively larger area within the lesion, which may explain the higher number of subsurface lesions observed.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of the varnishes: The peptide used in this study (PGEKADRAEKADRA) 24 was synthesized commercially at >98% purity (GenScript Biotech Corp. NJ, USA). Natural colophony was used to prepare the peptide-containing varnishes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Daha güncel bir çalışmada, amelogeninde ve mineralizasyonda rol alan diğer çoğu proteinde gözlemlenen bitişik zıt yüklü amino asitlerin varlığından yola çıkılarak tasarlanan 14 amino asitlik daha kısa ve mineral oluşum kinetiğini ADP5'e göre daha fazla artıran bir peptit elde edilmiştir. 22 Mineral promoting peptide-3 (MPP3) adı verilen bu peptit bir vernik içerisinde yapay mine lezyonlarına uygulandığında lezyon derinliğinde sadece flor içeren verniklere eşdeğer bir azalma sağlamıştır. Florla kombine edilerek kullanıldığında ise lezyon derinliğinde sadece flor içeren verniklere göre daha fazla azalma sağlamıştır.Yine adheziv uygulaması öncesinde dentin yüzeyi MPP3 ile muamele edildiğinde adhezyonu artıran ve mikrosızıntıyı azaltan bir mineral tabakası oluşturduğu gösterilmiştir.…”
Section: Introductionunclassified